AN EVENT STUDY: INDONESIAN CAPITAL MARKET REACTION TO THE RUSSIA-UKRAINE WAR ANNOUNCEMENT - Nurhaflah Soraya (JRAK, 2023)
The development of the Indonesian capital market is heavily influenced by global macroeconomics and economic conditions. The purpose of this study is to evaluate the reaction of the Indonesian capital market to LQ45 stocks before and after the announcement of war between Russia and Ukraine on February 24, 2022. The Composite Stock Price Index (IHSG) and the daily closing price of the corporation are utilized as secondary data. In this study, hypotheses were evaluated using the Wilcoxon signed-rank test and the one-sample t-test. The data indicated that the Indonesian capital market’s response to the Russia-Ukraine conflict was neglible, although abnormal returns in the mining, finance, consumer, and real estate sectors differ significantly.